Bend curve characteristics of phenol formaldehyde resin treated oil palm wood (Elaeisguineensis Jacq.) - Lawrence Insol, Alik; Edi Suhaimi, Bakar; Zaidon, Ashaari; Putri NurKhairunnisha, Ismail; Ronald Lian, Nuh; Gaddafi, Ismaili (Faculty of Science, University of Lagos, Nigeria, 2016)
It is discovered that oil palm wood (OPW) could be used as wood alternative material upon properly treated. The properties and appearance of OPW can be improved through impregnation treatment with low molecular weight phenol formaldehyde resin, resulting excellent material suitable for furniture and other special applications. It is often that for such applications, the materials are applied in or needs to be shaped curve, but the treated OPW is very rigid material. Although resin treated OPW can be made curved in the development, yet no comprehensive study on this matter has been done. Therefore, the objective of this study is to know how far the treated OPW can be bending without any defect and how it should achieved. In this first stage of the study, there are two variables were used the initial thickness and the moisture content of the sample before final microwave heating and three parameters were observed namely external defect, internal defect and bend curve fixation angle. The results showed that the treated OPW can be bend curve and both variables gave significant effect to the minimum acceptable curvature radius of the sample. It was found that a smaller diameter curve needs thinner initial thickness can be made to the sample within15-30 mm initial thickness at 70-80% moisture content before microwave heating.